2018
DOI: 10.1051/limn/2018019
|View full text |Cite
|
Sign up to set email alerts
|

The early catfish catches the worm: predation of Corydoras aeneus (Siluriformes, Callichthyidae) on freshwater nematodes

Abstract: In this study, we measured the daily consumption of four different nematode species by a small freshwater catfish species, Corydoras aeneus (Gill, 1858). Consumption of nematodes by fishes was significant with a single C. aeneus individual being able to consume in 24 h between 40 581 and 75 849 adult nematodes depending on the nematode species offered. This represented the ingestion of up to 238 mg wet weight when considering the largest nematode species: Panagrellus redivivus. Our results strengthen the growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In those laboratory experiments on the quantifications of nematode consumption by different fish species, only single nematode densities were offered. Spieth et al (2011), Weber & Traunspurger (2014a), and Majdi et al (2018) showed that in particular bottom-biting fish like common carps (3-4 cm body length), gudgeon (2.5-5 cm), and armored catfish (2-3 cm) are able to consume considerable amounts of nematodes (Caenorhabditis elegans) as shown by feeding rates of 234,000, 183,000, and 76,000 nematodes per day, respectively. At a body length of 9-12 cm (carps) and 10-12 cm (gudgeons), their nematode ingestion was reduced by 14% and 6% and was caused by increasingly larger meshes of the gill apparatus.…”
Section: Analyzed Thementioning
confidence: 99%
“…In those laboratory experiments on the quantifications of nematode consumption by different fish species, only single nematode densities were offered. Spieth et al (2011), Weber & Traunspurger (2014a), and Majdi et al (2018) showed that in particular bottom-biting fish like common carps (3-4 cm body length), gudgeon (2.5-5 cm), and armored catfish (2-3 cm) are able to consume considerable amounts of nematodes (Caenorhabditis elegans) as shown by feeding rates of 234,000, 183,000, and 76,000 nematodes per day, respectively. At a body length of 9-12 cm (carps) and 10-12 cm (gudgeons), their nematode ingestion was reduced by 14% and 6% and was caused by increasingly larger meshes of the gill apparatus.…”
Section: Analyzed Thementioning
confidence: 99%